ANALISIS PENGOPTIMALAN KEPEMIMPINAN PARTISIPATIF UNTUK MENINGKATKAN KUALITAS PELAYANAN PAJAK PADA KANTOR PELAYANAN, PENYULUHAN DAN KONSULTASI PERPAJAKAN (KP2KP) GUNUNGSITOLI - Halawa, Setiaman; Ndraha, Ayler Beniah (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. Participative leadership is leadership that provides significant space and roles to subordinates in carrying out decision-making process activities. Participative is related to the level of maturity from medium to high. A follower or subordinate at this level of development has the ability but not the desire to perform a given task. Their unwillingness is often due to a lack of confidence. However, the Head of KP2KP Gunungsitoli has not been optimal in carrying out participatory leadership to improve service quality at KP2KP Gunungsitoli. Where the Head of KP2KP Gunungsitoli seems less assertive in conveying important information and less involved in developing the skills and career opportunities of employees and PPNPN. This study aims to determine the strategy of optimizing participatory leadership to improve the quality of tax services. Based on the research results, the strategies for optimizing participatory leadership to improve the quality of tax services are providing training, development and additional learning to employees and PPNPN on a regular basis, evaluating employees and PPNPN on a regular basis, building a work culture that encourages collaboration, where employees are valued for their contribution in sharing knowledge and working together to achieve common goals, making the decision-making process and tax implementation more transparent and accountable, ensuring that tax guides, brochures, and other information provided to taxpayers are easy to understand and available online or offline.